1981
DOI: 10.1161/01.hyp.3.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt on prostaglandin metabolism in hypertension-prone and -resistant Dahl rats.

Abstract: SUMMARY The effect of high salt intake on rascular and renomedullary prostaglandin (PG) synthesis was compared in Sprague-Dawley and salt-sensitive (S) and -resistant (R) Dahl rats. Animals were given a diet containing either 0.6% or 8% NaCI starting at 5 weeks of age, and were sacrificed 6 weeks later. Systolic blood pressure of S rats increased to 220 ± 7 mm Hg but was unaffected in R and Sprague-Dawley rats. Prostaglandin synthesis was studied in aortic rings and renomedullary mlcrosomes using 14 C-arachido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…8,9 It should be noted that such an activation of prostanoid formation was absent in prehypertensive SHRs 11,12 or in salt-sensitive Dahl rats fed on a low-salt diet. 8,9 This result suggests that prostanoid synthesis is enhanced as a consequence of high BP and/or underlying hypertensive mechanisms. In addition, the acute COX inhibition by indomethacin increased the vascular resistance in perfused SHRs' hindlimbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 It should be noted that such an activation of prostanoid formation was absent in prehypertensive SHRs 11,12 or in salt-sensitive Dahl rats fed on a low-salt diet. 8,9 This result suggests that prostanoid synthesis is enhanced as a consequence of high BP and/or underlying hypertensive mechanisms. In addition, the acute COX inhibition by indomethacin increased the vascular resistance in perfused SHRs' hindlimbs.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the magnitude of the BP response to acute inhibition of NO synthase by N G -nitro-L-arginine methyl ester (L-NAME) injection is preserved in both salt and spontaneous hypertension, 1,4 but NO-dependent vasodilatation is clearly insufficient in compensating for major sympathetic hyperactivity, indicating a relative NO deficiency in rats with these forms of hypertension. 6,7 The synthesis and/or release of vasodilator prostanoids (namely prostacyclin (PGI 2 )) has been found to be increased in the blood vessels of Dahl salt-hypertensive (DS-HS) rats, 8,9 DOCA-salt hypertensive rats and spontaneously hypertensive rats (SHRs), 10,11 but not in prehypertensive SHRs. 11,12 Few attempts have been made to evaluate the contribution of these prostanoids to BP regulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the salt sensitivity can be transferred from S to R animals by the transplantation of a S strain kidney (Dahl et al 1974), suggesting the kidney plays a major role in this model of hypertension. Urinary excretion (Sustarsic et al 1981), renal papillary levels (Tobian et al 1982) and renomedullary synthesis of prostaglandin E2 (Limas et al 1981) are reported to be lower in S than in R rats. However, there are no available data about the characteristics of renal cytochrome P450 arachidonate metabolites in Dahl rats.…”
Section: Roles In Dahl Salt-sensitive Rats and Other Modelsmentioning
confidence: 99%
“…7 The PGEj content of snap-frozen renal papillae was also less in the DS than in the DR, both before and after high salt diets. 8 Renal medullary microsomes from DS also underproduced PGEj as compared with microsomes from DR. 9 Reduction of medullary PGEj may be important in the defective natriuresis observed in the DS strain. Prostaglandins have a role in promoting natriuresis in the inner medullary collecting duct in volume-expanded rats, 10 a situation somewhat analogous to high salt feeding.…”
mentioning
confidence: 99%